Is radioembolization (90Y) better than doxorubicin drug eluting beads (DEBDOX) for hepatocellular carcinoma with portal vein thrombosis? A retrospective analysis. (September 2015) - Akinwande, Olaguoke; Kim, Daniel; Edwards, Jacob; Brown, Russell; Philips, Prejesh; Scoggins, Charles; Martin, Robert C.G.
Abstract Introduction This study compares radioembolization (90Y) versus doxorubicin drug eluting beads (DEBDOX) in the treatment of unresectable hepatocellular carcinoma with portal vein thrombosis. Methods Using our prospectively maintained, multi-center, non-controlled intra-arterial therapy registry, we identified 28 consecutive patients with hepatocellular carcinoma (HCC) and portal vein thrombosis (PVT) treated with DEBDOX and 20 with 90Y. Follow-up protocol consisted of a 3-phase CT scan of the liver within 3 months post-treatment. Tumor response rates were measured according to modified Response Evaluation Criteria in Solid Tumors (mRECIST) criteria. Results There were 65 and 29 treatments in the DEBDOX and 90Y groups respectively. Median age of DEBDOX was 59.8 (35–81) and 90Y was 66.5 (49–82) years. A defined number of lesions were seen in 78% DEBDOX and 50% 90Y patients. Patients were similar in the remaining 8 baseline characteristics including performance status, Child Pugh and extent of PVT. There were fewer overall side effects in the DEBDOX group compared to the 90Y group (11% vs 39%; P = 0.03). There was better disease control (mRECIST) in the DEBDOX group compared to the 90Y group (67% vs 20%; P = 0.0014). Median survival times were 10 months in DEBDOX and 3 months in the 90Y group respectively from first treatment (log-rank, P = 0.037). Conclusion DEBDOX is safe for patients with HCC and PVT and may have lower toxicity than 90Y. It may also provide better disease control and survival benefit. Further studies are warranted to validate our observations and to determine if current clinical practice should be altered.